Molybdenum carbide embedded in carbon nanofiber as a 3D flexible anode with superior stability and high-rate performance for Li-ion batteries. Issue 7 (May 2018) - Lee, Gyo-Ho; Moon, Sang-Hyun; Kim, Min-Cheol; Kim, Si-Jin; Choi, Sojeong; Kim, Eun-Soo; Han, Sang-Beom; Park, Kyung-Won
Abstract: The fabrication process and material design of flexible lithium-ion batteries (LIBs) are essential in flexible portable devices. In particular, the carbon nanofiber (CNF)-based active anodes with flexibility synthesized using an electrospinning technique showed fairly stable cycling performance in the LIBs. In this study, we synthesized the molybdenum carbide (MoC) embedded in CNFs as an anode for LIBs (MoC/CNF) using an electrospinning technique with amorphous Mo precursor and polyacrylonitrile as the molybdenum and carbon sources, respectively, and using a heating process under an N2 atmosphere. The as-prepared flexible MoC/CNF showed a 3D porous structure consisting of crystalline MoC and amorphous CNF. MoC/CNF, directly utilized as an active electrode without binder, conductor, or current collector, exhibited superior LIB performance, i.e. high capacity, cyclability, and high-rate properties. In particular, at a considerably high charge/discharge rate of 10 A g −1, the specific capacity of MoC/CNF (109 mAh g −1 ) was significantly higher than that of pure CNF electrode (3 mAh g −1 ).